2019
DOI: 10.1136/bmjopen-2019-032025
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of the health of southern African truck drivers

Abstract: ObjectivesLifestyle and working conditions of truck drivers predisposes them to risk-factors associated with communicable and non-communicable diseases, but little is known about the health status of African truck driver. This study aims to assess a cross-section of truckers in South Africa to describe their health information.SettingThe study took place across three truck-stop rest areas in the South African provinces of Free State and Gauteng.ParticipantsEligibility criteria included being males aged 18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 32 publications
6
48
1
2
Order By: Relevance
“…Thirty-eight studies reported on smoking status. 3 11 18–21 23 27 34 36 38–42 46–49 53 54 56 63 65 69 70 72 77 80 82 83 86–89 91 96 97 103 Prevalence of current smokers ranged from 10% 73 to 72.9%, 83 however, categorising ‘current smokers’ varied between studies and was not defined in some. Jain et al found long haul truck drivers were more likely to smoke than delivery drivers, dock workers, mechanics or clerks.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-eight studies reported on smoking status. 3 11 18–21 23 27 34 36 38–42 46–49 53 54 56 63 65 69 70 72 77 80 82 83 86–89 91 96 97 103 Prevalence of current smokers ranged from 10% 73 to 72.9%, 83 however, categorising ‘current smokers’ varied between studies and was not defined in some. Jain et al found long haul truck drivers were more likely to smoke than delivery drivers, dock workers, mechanics or clerks.…”
Section: Resultsmentioning
confidence: 99%
“…The lifestyle and associated risk factors for NCDs greatly influnced by the Job and labor culture [ 12 ]. Truck driving is a job that lying drivers to risk factors for NCDs than other jobs [ 13 16 ]. Based on the above facts, this study aimed to assess the prevalence and associated factors of non-communicable diseases among cross-country truck drivers in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…Occupation and work culture influence the lifestyle and related risk factors for NCDs [ 12 ]. Truck driving is an occupation that prone drivers to risk factors for NCDs than other occupations [ 13 16 ]. Truck drivers are among those professionals whose job and health status greatly influences public safety.…”
Section: Introductionmentioning
confidence: 99%
“…It was higher than 40% in Manipal, India [ 21 ]. But, it was far lower than 64% in central North Carolina, USA [ 16 ], 69% in South Africa [ 22 ], 71% in India [ 23 ], 75.2% in Mexico [ 8 ], 76% in Germany [ 24 ], 79.2% in Brazil [ 18 ], 91.1% in Arkansas, USA [ 9 ], and 93.3% in the USA [ 25 ]. The variation observed is explained by the difference in socioeconomic and behavioral factors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted worldwide regarding the prevalence of abnormal BMI revealed that 40% in Manipal, India [ 21 ], 55.5% in Chennai, India [ 11 ], 64% in central North Carolina, USA [ 16 ], 69% in South Africa [ 22 ], 71% in India [ 23 ], 75.2% in Mexico [ 8 ], 76% in Germany [ 24 ], 79.2% in Brazil [ 18 ], 91.1% in Arkansas, USA [ 9 ], and 93.3% in the USA [ 25 ]. The factors that contribute to overweight and obesity are varied and might include age, income, educational status, nutrition, sleep duration, physical exercise, daily working hours, and years of driving experience [ 1 , 3 , 7 , 12 , 14 – 16 , 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%